Garimpo de silêncios experiências do trabalho de mulheres nas lavras diamantinas (Igatu/Andaraí-BA, décadas de 1930 a 1970) - Jesus, Daniella Silva dos Santos de (2019)
Following the trails and paths opened by the study of the Social History of Work and social relations of gender, from the point of view of what has come to be known as “history seen from beneath,” this study proposes an investigation of the working experience of women in artisan diamond mines in the district of Igatu, formerly known as the village of Chique-Chique, located in the city of Andaraí, Bahia, Brazil, during the period between 1930 and 1970. Using a qualitative approach, whose analysis is guided by the methodological basis of Oral History, aligned with documentary and bibliographical research, under the aegis of dialectical historical materialism, this study seeks to recompose the forms of insertion and working conditions, as well as the strategies constructed by women to enter and remain in artisan mining, weighing the repercussions which sexual division of labor imposed upon them. This study defends the hypothesis that work developed by women, whether in activities socially characterized as feminine or in activities linked to commerce and artisan mining that were viewed as “work for men and by men,” was a balancing factor on the “tightrope of survival,” especially in times of economic crisis which characterized the time frame. The resurgence of the mining activity in which much of the population was engaged brought about greater malleability and insertion of women in the extraction of diamonds. If, in normal situations, the income earned by women was considered complementary to that of men, during crises, it became essential to the survival of the artisan miner families. Considering the turbulent political and economic context and the complexities and peculiarities involved in the areas of mining, in addition to working conditions and relationships, women’s “meager wages” became the primary source of income available in poor families, thus establishing them as the main providers without their homes. Employing categories of analysis of experience, gender, and sexual division of labor, and using literary and especially oral sources as a reference, this study found that, although women were immersed in unequal gender relations, characterized by hierarchical social roles, in their experience of concrete life, these women, whether of their own free will and/or under pressure from the force of historical circumstances, improvised and redefined their practices and thoughts. In this daily struggle, they constituted new social roles, by assuming, for instance, the management of their homes, a condition reached as a result of the activities they developed. By means of their needs and experiences, they went against common sense and proved that artisan mining was also a place for women.